2018
DOI: 10.1891/1946-6560.9.4.313
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Electronic and In-Person Dating Violence Victimization, Anxiety, and Depression Among College Students in Hawai’i

Abstract: Among the college-age population, social media and other forms of electronic communication have become commonplace. This population is also considered at high risk for dating violence experiences; however, the intersection of electronic use and dating violence has only begun to be explored with this age group. This study sought to add to the understanding of technology use in dating relationships by examining electronic dating violence (EDV), as well as in-person dating violence and mental health symptoms. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
3
5
0
1
Order By: Relevance
“…We collected data using a semi-structured interview guide developed for evidence-based studies on cyberbullying and EDV ( Bennett et al, 2011 ; Hinduja and Patchin, 2011 ; Zweig et al, 2013b ; Dick et al, 2014 ; Brem et al, 2015 ; Reed et al, 2017 ; Marganski and Melander, 2018 ; Weingarten et al, 2018 ) and information provided by female students during a study on cyberbullying and violence against women (VAW) ( Alrawashdeh, 2020 ; Alsawalqa, 2021 ). Participants were interviewed face-to-face or via telephone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected data using a semi-structured interview guide developed for evidence-based studies on cyberbullying and EDV ( Bennett et al, 2011 ; Hinduja and Patchin, 2011 ; Zweig et al, 2013b ; Dick et al, 2014 ; Brem et al, 2015 ; Reed et al, 2017 ; Marganski and Melander, 2018 ; Weingarten et al, 2018 ) and information provided by female students during a study on cyberbullying and violence against women (VAW) ( Alrawashdeh, 2020 ; Alsawalqa, 2021 ). Participants were interviewed face-to-face or via telephone.…”
Section: Methodsmentioning
confidence: 99%
“…Among university students, EDV victimization was correlated with mental health symptoms, including depression, anxiety, and distress. Moreover, EDV victims experience higher levels of hostility and stress, uncertainty regarding relationships, feelings of loneliness, antisocial behaviors ( Bennett et al, 2011 ; Hinduja and Patchin, 2011 ; Weingarten et al, 2018 ; Galende et al, 2020 ), and sexual coercion ( Zweig et al, 2013b ). Furthermore, EDV predicted psychological and physical violence among sexual partners during personal encounters ( Brem et al, 2015 ; Marganski and Melander, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the extant literature focuses on face-to-face intimate partner violence and its negative effects on a victim's mental health; in contrast, lesser is known about its cyber variant: intimate partner cyberviolence (C. Brown & Hegarty, 2018;Gámez-Guadix, Borrajo, & Calvete, 2018). Despite the limited research, in the past few years there has been noticeable progress in the investigation of cybervictimization by an intimate partner (henceforth referred to as cyber IPV) and the ensuing mental health problems, such as depressive symptoms (Charak, Villarreal, Schmitz, Hirai, & Ford, 2019;Drouin, Ross, & Tobin, 2015;Weingarten, Wu, Gates, Carreno, & Baker, 2018;Wolford-Clevenger et al, 2016).…”
Section: Unique Additive and Interactive Effects Of Types Of Intimamentioning
confidence: 99%
“…Although few in number, studies suggest that cyber IPV is a form of intimate partner victimization that is associated with symptoms of depression and anxiety, symptoms of posttraumatic stress disorder (PTSD), antisocial behavior, and alcohol and substance use (Bennett, Guran, Ramos, & Margolin, 2011;Borrajo & Gámez-Guadix, 2016;Dardis, Strauss, & Gidycz, 2019;Lindsay et al, 2016;Watkins et al, 2018;Weingarten et al, 2018). Drouin, Ross, and Tobin (2015) investigated cyber sexual coercion victimization among young adults and found that it was associated with an increase in symptoms of anxiety, depression, and traumatic stress.…”
Section: Cyber Ipv and Mental Health Problemsmentioning
confidence: 99%
“…Bu şiddet çeşitleri ilişki sürecinde genellikle birbirinin içine geçmiş durumda olup, her çeşit şiddet bir kere görüldükten sonra genellikle artarak devam eder (Aslan, Vefikuluçay, Zeyneloğlu, Erdost ve Temel, 2008). Tüm eğitim, sosyoekonomik düzey ya da kültürlerde görülme ihtimali olan flört şiddetinin (Martins vd., 2014), psikolojik sonuçları bağlamında ele alındığında kaygı, depresyon (Choi, Wong ve Fong, 2017;Garthe, Sullivan ve Behrhorst 2018;Holt ve Espelage, 2005;Weingarten, Wu, Gates, Carreño ve Baker, 2018) ya da travma sonrası stres gibi psikolojik iyi oluş hâlini tehdit eden sonuçları olduğu görülmektedir (Callahan, Tolman ve Saunders, 2003;Perangin-Angin, Wijono ve Hunga, 2021).…”
Section: Introductionunclassified